"Existentialist man" as a basis of the new humanism in the philosophy of M. Heidegger - Скиба, I. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article is devoted to the study of "existentialist man" as a basis of the new humanism in the philosophy of M. Heidegger. The task is carried out through consecutive analysis of two aspects (ontological and anthropological) of M. Heidegger’s philosophy, researching of existence as a way of man’s being in German thinker’s philosophy; revealing of specific relationships of man’s nature and humanism in accordance with the philosophy of M. Heidegger.